If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 5) + -3(2 + -7x) = 0 Reorder the terms: 4(5 + 2x) + -3(2 + -7x) = 0 (5 * 4 + 2x * 4) + -3(2 + -7x) = 0 (20 + 8x) + -3(2 + -7x) = 0 20 + 8x + (2 * -3 + -7x * -3) = 0 20 + 8x + (-6 + 21x) = 0 Reorder the terms: 20 + -6 + 8x + 21x = 0 Combine like terms: 20 + -6 = 14 14 + 8x + 21x = 0 Combine like terms: 8x + 21x = 29x 14 + 29x = 0 Solving 14 + 29x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 29x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 29x = 0 + -14 29x = 0 + -14 Combine like terms: 0 + -14 = -14 29x = -14 Divide each side by '29'. x = -0.4827586207 Simplifying x = -0.4827586207
| -7(z+8)=35 | | 2(x+6)=x+16 | | 5s(9s+4)=0 | | m^3-3m^2=4m-12 | | -(5x+8)-2x= | | 7=w(w-6) | | Z^2+2z-35=0 | | 3x-5=4x-19 | | 3y-(5y-4)= | | -7+6=7 | | 0=n(120-n)-50n | | -0.75y=12 | | 9x-3(5x-2)-15=4(2x-4)+10-5(x+3) | | 5(p+3)+9=3(p-2)6 | | 11x=143 | | 11x-3=4x+11 | | 13x-5=6x+23 | | 320=4l*w | | 3x^2+22x-45=0 | | x^2+5.2x+2.1=0 | | 4x^2+29x-24=0 | | x^3+2x^2-11x-12=0 | | n=4-9-5n | | X+4=3(x-2) | | 4x-6=x | | 57-7x=2x+15 | | 4x-6= | | 13-10x=123-45x | | 5x-12=-3-4 | | 42.3=1.5+3.2d | | S=3F-2 | | 5x+5=-115-7x |